Longitudinal study of melanocytic nevi in adolescents - Darlington, Steven; Siskind, Vic; Green, Lynn; Green, Adele (Journal of the American Academy of Dermatology, 2002)
Background: Although melanocytic nevi are the strongest known risk factors for melanoma, their etiology is not well understood. Objectives: This study was performed to assess the roles of constitutional pigmentary factors and sun exposure in the development of new nevi in adolescents. Methods: A cohort of 111 school children, aged 12 and 13 years at baseline, were followed up for 5 years. Whole-body counts of nevi of all sizes and detailed sun exposure histories were updated each year. Analyses of full-body nevus counts and of nevus counts on the face and neck region and on the shoulder and back region were undertaken by means of log-linear regression, allowing for repeated measures. Results: Mean whole-body nevus counts were 130.1 (SD = 69.9) in 1990 and 215.5 (SD = 127.1) in 1994. Shoulder and back counts were consistently higher than face and neck counts. Subjects with heavy shoulder freckling had increased nevus counts on all sites investigated, with a means ratio for whole-body counts of 1.11 (95% CI, 1.03-1.19), compared with those with no freckling. Those who spent all of their school lunch times in the midday sun had a means ratio of 1.62 (95% CI, 1.15-2.29) compared with those who spent very little time in the sun during the lunch period. Summer holiday sun exposure was not significantly associated with development of nevi in this adolescent cohort. Conclusion: The degree of freckling, especially on the shoulders, and habitual midday sun exposure, rather than holiday sun exposure, are significant determinants of melanocytic nevi in Queensland adolescents. (J Am Acad Dermatol 2002;46:715-22.)